2015
DOI: 10.1021/acs.cgd.5b00653
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features in Metal–Organic Nanotube Crystals That Influence Stability and Solvent Uptake

Abstract: Porous hybrid materials such as metal−organic nanotubes are of interest due to synthetic tunability, possibility for 1-D flow, and confinement of solvent molecules. In the current study, the stability and solvent selectivity of two hybrid materials with nanotubular arrays, (pip) 0.5 [(UO 2 )(HIDA)(H 2 IDA)]·2H 2 O (UIDA; IDA = iminodiacetate) and [(UO 2 )(PDC)(H 2 O)] (UPDC; PDC = pyridine dicarboxylate) were analyzed using X-ray diffraction, gas chromatography/ mass spectrometry, thermogravimetric analysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 58 publications
0
49
0
Order By: Relevance
“…The UMON material can be synthesized using either methanol or acetone as the co-solvent and we have previously reported that when the compound is synthesized with methanol, it rapidly degrades in a high humidity environment. 123 A similar study was performed here for the Cu(II)-UMON (1:3 starting ratio) synthesized with methanol and acetone co-solvents by exposing the material to a saturated environment for a two month period and monitoring the solid state materials by powder X-ray diffraction over the course of the reaction period (Figure 4.9). For the pure UMON material synthesized with methanol, the material degraded within one week, 123 but the Cu(II)-UMON compound formed in the same co-solvent remained crystalline in a high humid environment for the entire period.…”
Section: Structural Stability Under High Humiditymentioning
confidence: 86%
See 4 more Smart Citations
“…The UMON material can be synthesized using either methanol or acetone as the co-solvent and we have previously reported that when the compound is synthesized with methanol, it rapidly degrades in a high humidity environment. 123 A similar study was performed here for the Cu(II)-UMON (1:3 starting ratio) synthesized with methanol and acetone co-solvents by exposing the material to a saturated environment for a two month period and monitoring the solid state materials by powder X-ray diffraction over the course of the reaction period (Figure 4.9). For the pure UMON material synthesized with methanol, the material degraded within one week, 123 but the Cu(II)-UMON compound formed in the same co-solvent remained crystalline in a high humid environment for the entire period.…”
Section: Structural Stability Under High Humiditymentioning
confidence: 86%
“…123 A similar study was performed here for the Cu(II)-UMON (1:3 starting ratio) synthesized with methanol and acetone co-solvents by exposing the material to a saturated environment for a two month period and monitoring the solid state materials by powder X-ray diffraction over the course of the reaction period (Figure 4.9). For the pure UMON material synthesized with methanol, the material degraded within one week, 123 but the Cu(II)-UMON compound formed in the same co-solvent remained crystalline in a high humid environment for the entire period. Both the pure and doped UMON material synthesized with acetone also retained crystallinity during the experiment.…”
Section: Structural Stability Under High Humiditymentioning
confidence: 86%
See 3 more Smart Citations